Innovative Costume of the 21st Century: The Next Generation, Dmitry Rodionov, curated by A.A. Bakhrushin Museum. Issue 1 (1st June 2021) - Lynch, Julie
Innovative Costume of the 21st Century: The Next Generation, Dmitry Rodionov, curated by A.A. Bakhrushin MuseumState Historical Museum, A.A. Bakhrushin State Central Theatre Museum, Center for Contemporary Art MARS Moscow, Russia, 17 June‐2 October 2019